Islam Nusantara in Islamic Law Epistemology Perspective - Maimun Maimun (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2016)
Islam Nusantara is a symbol of geographical religious tendencies representing Indonesian context. This term has become popular since 2015 by congress momentum of NU in Jombang, an organization of ulama’, who are really experts in the field of islamic religion. However this arise discourse creats variance responses between pro and contra as the excess of the concept that estimated as deviative concept from the guidance of Prophet Muhammad, namely Islamic tendency by Arabic character. Therefore it appears a desire to examine this controversial concept epistemologically with the expectation to find a holistic conceptual foothold either axiomatic or historical, through the study of literature. There are two problems representing this study; First, how is the basic epistemology of Islam Nusantara and its sociological implication? Second, how is the epistemology of Islam Nusantara in the view of islamic law (usul fiqh)?. Based on these problems, it can be found some conclusion; first, this concept is a product of thought of Nahdlatul Ulama’ (NU)  based on their struggle value, ASWAJA and the islamization movement conducted by walisongo in Java. The implication of this pattern is moderation, tolerance, and awareness of nations plurality tendency that allow ‘al-Islamu Salihun Likulli Zaman wa Makan’ becomes really true.  Secondly, by looking at the historical fact and the way of messenger propaganda supported by normative foundation al-Quran and hadith, something that we called as Islam Nusantara is not wrong concept coming out of Islam, moreover in Islam itself also known a building of Islamic law epistemology (‘urf) giving special space on local culture to be a law as long as does not digress from axiomatic Islamic text.